2019
DOI: 10.1002/hep.30552
|View full text |Cite
|
Sign up to set email alerts
|

Bezafibrate Improves GLOBE and UK‐PBC Scores and Long‐Term Outcomes in Patients With Primary Biliary Cholangitis

Abstract: In Japan, bezafibrate (BF) is a second‐line agent for primary biliary cholangitis (PBC) that is refractory to ursodeoxycholic acid (UDCA) treatment. From a retrospective cohort (n = 873) from the Japan PBC Study Group, we enrolled 118 patients who had received UDCA monotherapy for at least 1 year followed by combination therapy with UDCA+BF for at least 1 year. GLOBE and UK‐PBC scores after UDCA monotherapy (i.e., immediately before UDCA+BF combination therapy) were compared with those after 1 year of UDCA+BF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 47 publications
2
73
0
1
Order By: Relevance
“…There was a significant improvement of both UK‐PBC and GLOBE scores in the fibrate/UDCA group, but no improvement in the UDCA group. Recently, a Japanese retrospective study and the post hoc analysis of BEZURSO trial have shown improvement in both UK‐PBC and GLOBE scores after fibrate treatment, which is consistent with our study. Along with these studies, our current study implies that there may be a survival benefit from long‐term fibrate treatment in UDCA‐refractory PBC patients.…”
Section: Discussionsupporting
confidence: 92%
“…There was a significant improvement of both UK‐PBC and GLOBE scores in the fibrate/UDCA group, but no improvement in the UDCA group. Recently, a Japanese retrospective study and the post hoc analysis of BEZURSO trial have shown improvement in both UK‐PBC and GLOBE scores after fibrate treatment, which is consistent with our study. Along with these studies, our current study implies that there may be a survival benefit from long‐term fibrate treatment in UDCA‐refractory PBC patients.…”
Section: Discussionsupporting
confidence: 92%
“…However, ADRs that include increased serum creatinine kinase levels and myalgia have been reported in a bezafibrate add‐on group . Another study from Japan did not mention the ADRs of bezafibrate add‐on as a study limitation . In the current investigation, no severe ADRs were recorded for pemafibrate.…”
Section: Discussionmentioning
confidence: 59%
“…11,12 An inadequate response to UDCA is associated with a high risk of disease progression. Bezafibrate addition to UDCA therapy, which recently showed a favorable biochemical response in refractory PBC, 13,14 has been recommended for UDCAunresponsive patients by the Japan Society of Hepatology (JSH) guidelines. 8 However, there remain patients who are resistant to alternative medicinal therapies; other options are needed to treat such cases in an effort to halt PBC progression.…”
Section: Introductionmentioning
confidence: 99%
“…Co-administration of bezafibrate and UDCA to patients who had an incomplete response to UDCA treatment alone, significantly improved hepatic function and reduced liver fibrosis [202][203][204]. A retrospective cohort study correlated bezafibrate with UDCA combined therapy with reduced risk for liver transplantation and liver-related death [205]. Thus, the combined therapy may improve long-term prognosis of PBC patients.…”
Section: Primary Biliary Cholangitismentioning
confidence: 99%